2013
DOI: 10.5154/r.rchscfa.2012.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Estructura Y Composición Arbórea De Un Fragmento De Bosque Mesófilo De Montaña en El Estado De Veracruz

Abstract: La estructura y composición arbórea se analizaron en un fragmento de bosque mesófilo de montaña en la zona centro del estado de Veracruz. Para ello, se establecieron tres transectos de 2,000 m2, en los cuales se tomaron datos dasométricos a todos los individuos con diámetro normal mayor de 10 cm. Se encontraron 239 individuos pertenecientes a 14 especies, 12 géneros y 12 familias. La familia Fagaceae fue dominante en las áreas de muestreo. Quercus salicifolia, Liquidambar styraciflua, Quercus leiophylla y Alch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
1
5
1
3
Order By: Relevance
“…Our results indicated that the most important hotspots for the 12 tree species were patches 2 and 3, where 12 such species are likely co-distributed (Fig. 3); these cloud forest patches, in the states of Veracruz, Puebla, and Hidalgo, hold important diversity (García-De la Cruz et al, 2013;García-Franco et al, 2008;González-Espinosa, 2011;Williams-Linera, 2002;Williams-Linera et al, 2013), mainly in a beta-diversity sense, which is most important for Mexican cloud forest biotas (Carvajal-Hernández et al, 2014;Williams-Linera et al, 2013).…”
Section: Discussionmentioning
confidence: 76%
“…Our results indicated that the most important hotspots for the 12 tree species were patches 2 and 3, where 12 such species are likely co-distributed (Fig. 3); these cloud forest patches, in the states of Veracruz, Puebla, and Hidalgo, hold important diversity (García-De la Cruz et al, 2013;García-Franco et al, 2008;González-Espinosa, 2011;Williams-Linera, 2002;Williams-Linera et al, 2013), mainly in a beta-diversity sense, which is most important for Mexican cloud forest biotas (Carvajal-Hernández et al, 2014;Williams-Linera et al, 2013).…”
Section: Discussionmentioning
confidence: 76%
“…94.13.51.40.80.2Fortanelli-Martínez et al., 2014 Podocarpus reichei J. Buchholz & N.E. Gray92.14.22.21.40.2Alcántara and Luna, 1997 Eugenia xalapensis (Kunth) DC.90.75.92.01.10.3García-De La Cruz et al., 2013 Carya ovata (Mill.) K.Koch 94.42.81.51.00.3Valdez et al., 2003 Carpinus caroliniana Walter 89.45.83.01.50.3Catalán et al., 2003 Platanus mexicana Moric.80.713.33.91.70.4Arellano et al., 2005 Quercus eugeniifolia Liebm.96.32.01.00.60.1Alcántara and Luna, 2001 Oreopanax xalapensis (Kunth) Decne.…”
Section: Methodsmentioning
confidence: 99%
“…& Planch89.56.42.71.20.1Catalán et al., 2003 Clethra alcoceri Greenm.93.43.71.80.90.2Alcántara and Luna, 2001 Cornus disciflora Moc. & Sessé ex DC.91.64.62.31.30.2Luna et al., 1994 Ostrya virginiana (Mill) K. Koch88.66.23.01.90.3Fortanelli-Martínez et al., 2014 Liquidambar styraciflua L.94.12.71.51.40.2García-De La Cruz et al., 2013 Ternstroemia lineata DC.98.70.60.40.30.0Rubio-Licona et al., 2011 Persea schiedeana Nees95.02.81.20.80.3Lorea-Hernández, 2002 Cyathea mexicana Schltdl. & Cham.93.13.91.61.00.4Luna et al., 1994∗Environmental suitability refers to the potential distribution area of each species, presented here in five classes, with 0–0.2 null as the no distribution potential category and 0.81–1.0 the highest potential category.…”
Section: Methodsmentioning
confidence: 99%
“…Vegetation consists of second growth vegetation and abandoned coffee plantations (Tolome, 1993;Williams-Linera, 1993). The shade coffee plantation (19 • 27 32 N, 96 • 59 26 W; 1210-1313 m asl; 10 ha) is characterized by the presence of some cloud forest elements as well as some exotic plant species (García-De la Cruz et al, 2013;López-Goméz, 2004 …”
Section: Study Areamentioning
confidence: 99%